2013
DOI: 10.1002/stem.1474
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-20 and mirna-106a regulate spermatogonial stem cell renewal at the post-transcriptional level via targeting STAT3 and Ccnd1

Abstract: Studies onspermatogonial stem cells (SSCs) are of unusual significance because they are the unique stem cells that transmit genetic information to subsequent generations and they can acquire pluripotency to become embryonic stem-like cells that have therapeutic applications in human diseases. MicroRNAs (miRNAs) have recently emerged as critical endogenous regulators in mammalian cells. However, the function and mechanisms of individual miRNAs in regulating SSC fate remain unknown. Here we report for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
145
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 53 publications
6
145
0
3
Order By: Relevance
“…Collectively, these findings suggest that miR-17-92 clusters play potential roles in maintaining the stemness of SSCs. Consistent with these observations, we have recently demonstrated that miR-20 and miR-106a are required for the proliferation and survival of mouse SSCs through targeting Stat3 and Ccnd1 (He et al 2013).…”
Section: The Roles Of Mirnas In Ssc Self-renewal and Differentiationsupporting
confidence: 80%
“…Collectively, these findings suggest that miR-17-92 clusters play potential roles in maintaining the stemness of SSCs. Consistent with these observations, we have recently demonstrated that miR-20 and miR-106a are required for the proliferation and survival of mouse SSCs through targeting Stat3 and Ccnd1 (He et al 2013).…”
Section: The Roles Of Mirnas In Ssc Self-renewal and Differentiationsupporting
confidence: 80%
“…Several miRNAs are responsible for mouse SSC/SPC maintenance and differentiation, including miR-21, miR-17-92, miR-106b-25, miR221/222, miR-34c, miR-146, miR-let7s, miR-20 and miR-106a (Niu et al 2011, Tong et al 2011, He et al 2013, Huszar & Payne 2013, Yang et al 2013, Chakraborty et al 2014, Wu et al 2014, Yu et al 2014. Compared with THY1 K spermatogonia, miR-21 is highly expressed in THY1 C SSC/SPCs and is regulated by ETV5 in THY1…”
Section: Small Non-coding Rnas In Ssc/spc Maintenance and Differentiamentioning
confidence: 99%
“…miR-221/222 is required for the maintenance of the undifferentiated state because it negatively regulates c-Kit expression and the inhibition of miR-221/ 222 results in the stimulation of differentiation associated with the loss of stem cell capacity in THY1 C cells in vitro (Yang et al 2013). Similar to miR-221/222, miR-20 and miR-106a from the miR-17-92 cluster play roles in SSC/ SPC self-renewal that may be partly mediated through targeting and down-regulating the spermatogonial differentiation factor STAT3 (He et al 2013). miR-146 is highly expressed in THY1 C GFRA1 C cells compared with c-KIT C differentiated spermatogonia.…”
Section: Small Non-coding Rnas In Ssc/spc Maintenance and Differentiamentioning
confidence: 99%
“…5). К ним относят популяции гоноцитов и сперматогониев у мышей [41], Thy1(+)-кле-точные популяции, состоящие в основном из сома-тических клеток семенников, и Thy1(-)-клеточные популяции [42], сперматогониев GFRα(+) (рецептора, рас полагающегося исключительно на поверхности не-дифференцирующихся сперматогониев) и спермато-гониев GFRα(-) [43].…”
Section: этапы сперматогенезаunclassified
“…Показано, что гены микроРНК-21, наряду с микро- [42]. Гены и микроРНК-20 и -106а также преимущест-венно транскрибируются в ССК и участвуют в диффе-ренцировке сперматогониальных клеток на посттран-скрипционном уровне, поскольку имеют таргетные области связывания с мРНК Stat3 и CyclinD1 [43]. Ген микро РНК-146 также выражено экспрессируется в не-дифференцированных сперматогониях, так как в диф-ференцированных сперматогониях уровень его экспрес-сии снижается почти в 180 раз [66].…”
Section: этапы сперматогенезаunclassified